Public Employment and Compensation Reform During Times of Fiscal Consolidation - Forni, Lorenzo (IMF Working Papers; Working Paper, 2014)
This paper compiles and compares recent and past measures introduced to contain the public wage bill in a number of emerging and advanced economies to assess their effectiveness in bringing down expenditure in a sustained way. In the aftermath of the Great Recession a number of countries have approved measures on the wage bill as part of fiscal consolidation efforts. These recent episodes are compared to past cases implemented in advanced economies over the period 1979-2009. Findings suggest that public wage bill consolidation episodes pre and post 2009 are similar in many respects. Moreover, typically countries that were able to achieve more sustained reductions in the wage bill have implemented to larger extent structural measures, and/or these measures were accompanied with substantial social dialogue and consensus.